(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This study explores the characterization of deep-level parameters in silicon through capacitance spectroscopy techniques. Deep-level defects play a crucial role in determining the electrical properties of silicon-based devices, impacting their performance in a variety of applications, including sensors, transistors, and photovoltaics. Capacitance spectroscopy offers a non-destructive method to identify and quantify these deep-level defects by analyzing the capacitance-voltage characteristics of semiconductor materials. The paper discusses the theoretical foundations of capacitance spectroscopy, the experimental setup used for measurements, and the interpretation of results to extract key parameters such as defect energy levels, capture cross-sections, and concentration profiles. Through comprehensive analysis, this work contributes to a better understanding of the behavior of deep-level defects in silicon, providing valuable insights for optimizing material properties and enhancing device reliability.